Viralitas Informasi di TikTok dalam Membentuk Opini Mahasiswa terhadap Figur Politik: Studi Kasus Bahlil Lahadalia - Nazatul Syimah; Suci Nurhasanah Harahap; Syarifah Fatimah Al-mutmainnah; Syifa Aulia Rahma Siregar (Universitas Negeri Medan, 2026)
This study examines the role of viral information on TikTok in influencing students' opinions about political figures. The study focuses on changes in public perception of Bahlil Lahadalia, who initially received widespread criticism due to the controversy surrounding the subsidized LPG policy, then gained appreciation through viral content on social media. Using a descriptive qualitative approach and case study method, the study found that the spread of information is influenced by the platform's algorithm, how the information is framed, and the public figure's response to criticism. The results indicate that students' opinions in the digital era tend to change easily following the flow of viral information.